A clinically meaningful fetal hemoglobin threshold for children with sickle cell anemia during hydroxyurea therapy. Issue 12 (28th September 2017) - Estepp, Jeremie H.; Smeltzer, Matthew P.; Kang, Guolian; Li, Chen; Wang, Winfred C.; Abrams, Christina; Aygun, Banu; Ware, Russell E.; Nottage, Kerri; Hankins, Jane S.
Abstract: Hydroxyurea has proven clinical benefits and is recommended to be offered to all children with sickle cell anemia (SCA), but the optimal dosing regimen remains controversial. Induction of red blood cell fetal hemoglobin (HbF) by hydroxyurea appears to be dose‐dependent. However, it is unknown whether maximizing HbF% improves clinical outcomes. HUSTLE (NCT00305175) is a prospective observational study with a primary goal of describing the long‐term clinical effects of hydroxyurea escalated to maximal tolerated dose (MTD) in children with SCA. In 230 children, providing 610 patient‐years of follow up, the mean attained HbF% at MTD was >20% for up to 4 years of follow‐up. When HbF% values were ≤20%, children had twice the odds of hospitalization for any reason ( P  < .0001), including vaso‐occlusive pain ( P  < .01) and acute chest syndrome (ACS) ( P  < .01), and more than four times the odds of admission for fever ( P  < .001). Thirty day readmission rates were not affected by HbF%. Neutropenia (ANC <1000 × 10 6 /L) was rare (2.3% of all laboratory monitoring), transient, and benign. Therefore, attaining HbF >20% was associated with fewer hospitalizations without significant toxicity. These data support the use of hydroxyurea in children, and suggest that the preferred dosing strategy is one that targets a HbF endpoint >20%.